2021
DOI: 10.3389/fcvm.2021.656702
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Transthoracic Contrast Echocardiography for the Diagnosis and Treatment of Idiopathic Pulmonary Arteriovenous Malformations

Abstract: Objective: To explore the preferred test to screen for pulmonary arteriovenous malformations (PAVMs) and to predict the probability of interventional embolization.Methods: We performed a retrospective observational study evaluating patients with idiopathic PAVMs from 2009 to 2019. After clinical evaluation, a total of 105 patients were studied, including 71 patients with positive digital subtraction pulmonary angiography (DSPA) findings and 34 with negative DSPA findings. The following patient data were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Moreover, the lower the TECE grade scales, the more often they are microscopic level PAVMS that are undetectable on radiologic. Several studies about the diagnostic value of TTCE in PAVMs published that the lower TTCE grade scale was associated with a lower prevalence of radiologic detectable PAVM ( 9 , 10 ). Since this study included relatively many patients with a small grade of TECE, low PPV was reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the lower the TECE grade scales, the more often they are microscopic level PAVMS that are undetectable on radiologic. Several studies about the diagnostic value of TTCE in PAVMs published that the lower TTCE grade scale was associated with a lower prevalence of radiologic detectable PAVM ( 9 , 10 ). Since this study included relatively many patients with a small grade of TECE, low PPV was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have already established effective screening tests for PAVM diagnosis in asymptomatic HHT patients. Transthoracic contrast echocardiography (TTCE) has high sensitivity (93–100%) for detecting PAVMs ( 3 , 8 10 ). Because complications associated with PAVMs also occur in even asymptomatic patients without HHT and because PAVMs can be effectively treated by percutaneous transcatheter embolization ( 11 ), the diagnosis of PAVMs that form an intrapulmonary right-to-left shunt in patients without HHT is important.…”
Section: Introductionmentioning
confidence: 99%